2023
DOI: 10.1186/s12888-023-04777-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based differences in interaction effects between childhood maltreatment and problematic mobile phone use on college students’ depression and anxiety symptoms

Abstract: Background Childhood maltreatment and problematic mobile phone use are risk factors for depression and anxiety symptoms among college students. However, how the interaction between the two factors affects depression and anxiety has yet to be validated. This study aimed to investigate the independent and interaction effects of childhood maltreatment and problematic mobile phone use on depression and anxiety among college students and explored gender-based differences in these associations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Ultimately, 7,617 valid samples were obtained, at an efciency rate of 96.8%. According to the previous survey results of the author’s research team, the prevalence of depression, anxiety, and co-morbidity of depression and anxiety symptoms were 20.0, 20.3, and 10.1%, respectively ( 13 ), and the calculation of study power inferred that 7,617 subjects could meet the needs of the design sample size of this study. A total of 2,312 (30.4%) were boys, and 5,305 (69.6%) were girls.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…Ultimately, 7,617 valid samples were obtained, at an efciency rate of 96.8%. According to the previous survey results of the author’s research team, the prevalence of depression, anxiety, and co-morbidity of depression and anxiety symptoms were 20.0, 20.3, and 10.1%, respectively ( 13 ), and the calculation of study power inferred that 7,617 subjects could meet the needs of the design sample size of this study. A total of 2,312 (30.4%) were boys, and 5,305 (69.6%) were girls.…”
Section: Methodsmentioning
confidence: 85%
“…Compared with students with either depression or anxiety symptoms, college students with comorbid anxiety and depression usually experience more stressful life events, worse emotional regulation ability, more severe physical and mental symptoms, more serious impairment of social functioning, and worse prognosis, making the comorbidities of depression and anxiety a key public health issue ( 12 ). As a result, there is increasing attention being paid to the factors that contribute to depression and anxiety symptoms, the comorbidity of these symptoms, as well as the interactions among these factors ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous epidemiological surveys found a high rate of mobile phone addiction among college students. For example, Zhang et al (12) found that the prevalence of problematic mobile phone use among Chinese university students was as high as 26.1%. As a systematic review reported, China was at the highest incidence of mobile phone addiction (13).…”
Section: Introductionmentioning
confidence: 99%